2022
DOI: 10.3389/fpubh.2022.795734
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Clustering Patterns and Population Characteristics of COVID-19 Based on Text Clustering Method

Abstract: BackgroundDescriptions of single clinical symptoms of coronavirus disease 2019 (COVID-19) have been widely reported. However, evidence of symptoms associations was still limited. We sought to explore the potential symptom clustering patterns and high-frequency symptom combinations of COVID-19 to enhance the understanding of people of this disease.MethodsIn this retrospective cohort study, a total of 1,067 COVID-19 cases were enrolled. Symptom clustering patterns were first explored by a text clustering method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Decrease in symptom burden has been previously observed in older age groups compared with younger (e.g. [ 32 ]), reflecting our results here. The identified symptom patterns among individuals with COVID-19 > 12 weeks ago were found to be strongly associated with length of time unable to function as normal due to COVID-19 symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Decrease in symptom burden has been previously observed in older age groups compared with younger (e.g. [ 32 ]), reflecting our results here. The identified symptom patterns among individuals with COVID-19 > 12 weeks ago were found to be strongly associated with length of time unable to function as normal due to COVID-19 symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…In the symptom clustering analyses, the data did not support more than two symptom patterns among any of the COVID-19 groups in any of the studies, though relatively small sample sizes in these groups may have affected our ability to identify further symptom patterns of low prevalence. Other studies using differing clustering methods and study designs have found greater than two symptom patterns annotated as distinct symptom sets when studying acute COVID-19 [ 32 , 33 ] and long COVID [ 34 ]. However, some studies have similarly found two symptom patterns to best fit the data: in the Norwegian Mother, Father and Child Cohort Study, Caspersen et al [ 1 ] analysed 73,727 adults followed throughout the pandemic and observed distinct patterns of post-acute symptoms characterised as ‘neurocognitive’ and ‘cardiorespiratory’.…”
Section: Discussionmentioning
confidence: 99%
“…In the symptom clustering analyses, the data did not support more than two symptom patterns among any of the COVID-19 groups in any of the studies, though relatively small sample sizes in these groups may have affected our ability to identify further symptom patterns of low prevalence. Other studies using differing clustering methods and study designs have found greater than two symptom patterns annotated as distinct symptoms sets when studying acute COVID-19 (32, 33) and long COVID (34). However, some studies have similarly found two symptom patterns to best fit the data: in the Norwegian Mother, Father and Child Cohort Study, Caspersen et al 2022 (1) analysed 73,727 adults followed throughout the pandemic and observed distinct patterns of post-acute symptoms characterised as ‘neurocognitive’ and ‘cardiorespiratory’.…”
Section: Discussionmentioning
confidence: 99%
“…[absent (0), mild (1), moderate (2), and severe (3)]. The study covered 33 symptoms; those like cough, fatigue, and running nose were referred from validated studies 7,9 ; other symptoms frequently occurring on social media were also included. These symptoms were divided into four syndromes: respiratory symptoms (nine types), neurological symptoms (nine types), digestive symptoms (eight types), and other symptoms (seven types).…”
Section: Questionnairementioning
confidence: 99%